Bones, Genetics, and Behavior of Rhesus Macaques Macaca Mulatta of Cayo Santiago and Beyond - Wang, Qian (Developments in Primatology: Progress and Prospects, 2012)
The introduction of rhesus macaques (Macaca mulatta) to Cayo Santiago, Puerto Rico in 1938, and the subsequent development of the Caribbean Primate Research Center (CPRC) for behavioral and biomedical research, has generated an unparalleled resource for physical anthropology and other fields in the social, biological, and medical sciences. Bones, Genetics, and Behavior of Rhesus Macaques: Macaca Mulatta of Cayo  Santiago and  Beyond  highlights recent and ongoing research in physical anthropology, and reveals the numerous research opportunities that still exist at this unusual rhesus facility.